DEMOTIVATING FACTORS AMONG INDONESIAN EFL TEACHERS - Lestari, Ika Wahyuni (Journal of Foreign Language Teaching and Learning, 2017)
Demotivation has been an issue in many EFL countries as revealed by many prior studies. However, limited studies were conducted to investigate it in Indonesian context, particularly in Indonesian higher education level. This qualitative study was done to investigate demotivators perceived by EFL teachers in Indonesia. To collect the data, three Non-English Department teachers were involved in a semi-structured interview. They were asked to share their perceptions and experiences on what demotivated them as teachers. The results showed nine factors causing demotivation among Indonesian college teachers. Teachers' poor physical fitness, students' negative attitudes, responses and behaviors, unfixed curriculum and school systems, poor salary, poor quality of school facilities, abundant administrative tasks, poor relationship among colleagues, inappropriate teaching materials, and lack of opportunity for professional development were reported as demotivators undergone by the teachers. The study was concluded by offering some implications to cope with demotivators.